Unveiling the Art of Nicknaming: Exploring Various Ways and Types (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the complex practice of nicknaming, a phenomenon in every culture worldwide. It explores the different types of nicknames, including the sociocultural functions they serve, and the various ways by which people create and assign nicknames. The research also delves into the psychological and social implications of nicknaming, considering how names can reflect identity, group membership, and relationships.